Frankie's fortune: buzzwords - Watts, Margaret; Guthridge, Bettina (Nelson ITP Melbourne, 1998)
"Frankie's Fortune" is an enchanting tale about a young boy named Frankie who discovers a mysterious fortune cookie that changes his life. As he opens the cookie, he finds a message that leads him on an unexpected adventure filled with surprises and challenges. Throughout the story, Frankie learns valuable lessons about courage, friendship, and the importance of believing in oneself. As he follows the clues, he encounters various characters who help him along the way, reinforcing the idea that fortune is not just about luck but also about the choices we make and the relationships we build. The narrative combines elements of humor and heart, ultimately celebrating the journey of self-discovery and the joy of embracing life's uncertainties.